Legal Review of donation-based crowdfunding system arrangements in Indonesia - Wandi Laiya (Estudiante Law Journal, 2026)
This article aims to find out how the legal review of the regulation of the donation-based crowdfunding system in Indonesia and find out how the legal responsibility of online fundraisers to the donation-based crowdfunding system in Indonesia. This research uses normative methods, and data sources are obtained from primary and secondary data, primary data consists of laws and regulations, and official records.  Dor secondary i.e. books, journals, and other relevant sources.  The results obtained from this study are that Indonesia already has regulatory instruments for donation collection activities, but has not fully guaranteed legal protection for donors considering that there are still unclear rules regarding the form and mechanism of enforcement against alleged misuse of donation funds. In addition, legal responsibility for the online donation-based crowdfunding system according to positive law in Indonesia has been in the form of accountability arrangements for platform operators, or fundraising in the form of annual financial statements by foundations to be audited by public accountants